In vivo genotoxicity and cytotoxicity assessment of a novel quinoxalinone with trichomonacide activity. Issue 12 (10th October 2012) - Rivera, Norma; Rojas, Marcela; Zepeda, Armando; Malagón, Filiberto; Arán, Vicente J.; Marrero‐Ponce, Yovani; Rivera, Ernesto; Fortoul, Teresa I.
ABSTRACT: The compound VAM2‐6 (1‐methyl‐7‐nitro‐4‐(5‐(piperidin‐1‐yl)pentyl)‐3, 4‐dihydroquinoxalin‐2(1H)‐one) has previously been shown to have an in vitro efficacy of 100% at a concentration of 100 µg ml –1 against Trichomonas vaginalis, a protozoon parasite that causes the sexually transmitted disease trichomoniasis. Because VAM2‐6 is a quinoxaline derivative and given the lack of studies on the genotoxic activity of this compound, the present study was undertaken to evaluate its ability to induce DNA damage in the peripheral blood of mice using single‐cell gel electrophoresis (SCGE or comet assay) and the micronucleus (MN) assay. Cell viability was assessed using a fluorochrome‐mediated viability test. The compound was tested on CD1 mice at 60, 40 and 10 mg kg –1 body weight administrated intraperitoneal (i.p.) in a single dose. Peripheral blood samples were collected 24 and 48 h after treatment. N ‐Ethyl‐ N ‐nitrosourea (ENU) was used as a positive control for the comet and micronucleus assays. The results showed that i.p. VAM2‐6 induced single‐strand DNA breaks and increased the average number of micronuclei in the treated mice in a dose‐dependent manner at 60, 40 and 10 mg kg –1 . Cell viability decreased at 24 h but recovered at 48 h for all three evaluated doses. Therefore, the chemical structure of VAM2‐6 should be modified to reduce its genotoxic potential. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Compound VAM2‐6, a 7‐nitro‐4‐(5‐piperidinopentyl)quinoxalin‐2‐one, has been shown previously to exhibit an in vitro trichomonacide efficacy of 100% at a concentration of 100 µg ml –1 . The present study was undertaken to evaluate its ability to induce DNA damage in the peripheral blood of mice using the comet and micronucleus assays. Cell viability was assessed by the fluorochrome‐mediated viability test. VAM2‐6 induced DNA damage in a dose‐dependent manner and decreased cell viability 24 h after treatment.